The Unwelcome Consuls: The Contested Appointment of Chinese Consuls in Colonial Malaya (KEMANUSIAAN The Asian Journal of Humanities, 2015)
The prospect of the appointment of Chinese Consuls for colonial Malaya following Britain's recognition of the People's Republic of China (PRC) in January 1950 illustrated the tension between Britain's colonial and international priorities in Southeast and East Asia. While the Foreign Office and its regional representatives were eager not to antagonise China by refusing to admit consuls to Malaya, the colonial authorities were alarmed by the fact that Chinese Consuls in Malaya would give succour to Chinese insurgents in Malaya. Confronted with the communist insurgency, British colonial administrators sought to delay and prevent the arrival of Chinese Consuls. This article examines the debates among the British policy makers within the imperial framework for British policies in the formative decade of the Cold War. It argues that the question of Chinese consular representation was contentious because of the colonial government's inability to secure the loyalty of the Chinese communities in the midst of the communist insurgency.